Mobile Museums Collections in circulation - Driver, Felix; Nesbitt, Mark; Cornish, Caroline (UCL Press, 2021)
Mobile Museums presents an argument for the importance of circulation in the study of museum collections, past and present. It brings together an impressive array of international scholars and curators from a wide variety of disciplines - including the history of science, museum anthropology and postcolonial history - to consider the mobility of collections. The book combines historical perspectives on the circulation of museum objects in the past with contemporary accounts of their re-mobilisation, notably in the context of Indigenous community engagement. Contributors seek to explore processes of circulation historically in order to re-examine, inform and unsettle common assumptions about the way museum collections have evolved over time and through space. By foregrounding questions of circulation, the chapters in Mobile Museums collectively represent a fundamental shift in the understanding of the history and future uses of museum collections. The book addresses a variety of different types of collection, including the botanical, the ethnographic, the economic and the archaeological. Its perspective is truly global, with case studies drawn from South America, West Africa, Oceania, Australia, the United States, Europe and the UK. Mobile Museums helps us to understand why the mobility of museum collections was a fundamental aspect of their history and why it continues to matter today. Praise for Mobile Museums 'This book advances a paradigm shift in studies of museums and collections. A distinguished group of contributors reveal that collections were not dead assemblages. The nineteenth and twentieth centuries were marked by vigorous international traffic in ethnography and natural history specimens that tell us much about colonialism, travel and the history of knowledge - and have implications for the remobilisation of museums in the future.' - Nicholas Thomas, University of Cambridge 'The first major work to examine the implications and consequences of the migration of materials from one scientific or cultural milieu to another, it highlights the need for a more nuanced understanding of collections and offers insights into their potential for future re-mobilization.' - Arthur MacGregor